APLIKASI KOMPOS TRICHODERMA DAN BIOCHAR DALAM MENINGKATKAN PRODUKSI PETANI BAWANG DI DESA DAYAH SUKON KABUPATEN PIDIE - Nasrullah; Zulwanis; Said Mirza Pratama; Muhammad Resthu; Samadi; Rina Sriwati; Darusman; Kevin Rizqullah El-Ryiad (LPPM Universitas Al Muslim, 2024)
Shallots are one of the leading commodities in Indonesia. The demand for shallots has increased, both for consumption and seeds, forcing Indonesia to import to meet these needs. Pidie Regency has been the center for shallot development in Aceh since 2019. This community service activity aimed to transfer knowledge and technology to farmers to produce compost and biochar independently in order to increase productivity and maintain the quality of land fertility. This activity is a demonstration plot for the implementation of the USK 2023 Kedaireka activities, in the fostered village of the Pionir Nusantara Foundation as a partner (Dayah Sukon Village, Pidie Regency) from August to November 2023. Mentoring activities were carried out through FGDs, providing knowledge about onion cultivation technology with sustainable microbial compost and biochar along with pest and disease management. Demonstration of good onion planting and production of Trichoderma and biochar compost and the application techniques were executed at the beginning of the activity. Proceeded with post-harvest and onion production results calculation based on farming efforts. Participants engaged in the activity enthusiastically, asking questions and telling stories about the cultivation practices they have done, learning how to make Trichoderma and biochar compost as well as the problems. Participants planted onion seeds using the land they have. Demonstration plots of sustainable onion cultivation practices with Trichoderma compost and Biochar in fostered villages increase production by 1:15, denoting that 1 kg of seeds produces 15 kg of onion bulbs. This effort is made to drive onions as primary commodity to support the community's economy and increase farmers' income, and be replicated by other farmers to invigorate Pidie Regency as the center for Aceh's shallots production.